2015
DOI: 10.1590/1678-775720150102
|View full text |Cite
|
Sign up to set email alerts
|

Motor, linguistic, personal and social aspects of children with Down syndrome

Abstract: A global developmental delay is expected from Down syndrome, affecting motor, cognitive, linguistic and personal-social skills. However, not always these delays are proportional; different conditions occur due to several intrinsic and extrinsic variables that must be controlled to form groups of greater homogeneity. Objective To enhance personal-social, fine motor-adaptive, gross motor and linguistic skills among children with Down syndrome and compare them with typically developing children, matched for gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
0
31
0
3
Order By: Relevance
“…Additionally, a research on "motor, linguistic, personal and social aspects of children with Down's syndrome" found that a statistically significant difference was verified between groups for language and fine-motor adaptive areas. That is to say, children with Down's syndrome show lower performance in language and fine motor skills when compared to typical developing children, but there was no statistically significant difference in gross motor or personal-social areas (Ferreira-Vasques & Lamonica, 2015). The results of these researches pointed to the problems of fine motor skills in children with Down's syndrome.…”
Section: Introduction To the Problemmentioning
confidence: 82%
“…Additionally, a research on "motor, linguistic, personal and social aspects of children with Down's syndrome" found that a statistically significant difference was verified between groups for language and fine-motor adaptive areas. That is to say, children with Down's syndrome show lower performance in language and fine motor skills when compared to typical developing children, but there was no statistically significant difference in gross motor or personal-social areas (Ferreira-Vasques & Lamonica, 2015). The results of these researches pointed to the problems of fine motor skills in children with Down's syndrome.…”
Section: Introduction To the Problemmentioning
confidence: 82%
“…The motor development of infants with DS is expected to be impaired 2,3 . However, when considering that the motor development is influenced by the home environment, our results showed that home affordances have a positive relationship with the motor performance of infants between 12 and 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…Campos et al 20 compared infants with DS to typical infants and found that infants with DS performed fewer interaction activities with the environment. This can be explained by limitations in motor skills, such as deficits in postural and antigravity control 2,3 . Therefore, we can consider that in addition to precarious home affordances, DS limitations interfere in motor performance 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DS is caused by trisomy for chromosome 21 (Hsa21) and is associated with several well established morbidities including cardiac defects, growth anomalies, endocrinopathies, ophthalmologic disorders and learning disabilities (1-5). Despite the fact that children with DS have a higher risk for malignant neoplasms (6), the incidence of solid tumors in people with DS is actually lower than in the population without DS, including all age groups (7, 8).…”
Section: Clinical Features and Treatment Of Ds-allmentioning
confidence: 99%